Reflections on resource-based learning environments: continuing the exploration of opportunities and obstacles. (5th March 2007) - Hill, Janette R.
The digital age has led to several changes in the nature of information resources. The very nature of the media and the ubiquitous presence of enabling technologies in classrooms, libraries, homes, businesses and communities have assisted with propelling the transformation. The implications of this change for education have been somewhat nebulous. While some recognise the promise for teaching and learning in the digital age, the methods and strategies used remain largely unchanged. The purpose of this paper is to provide a framework for thinking about the design of learning environments based on a resource-based model. Firstly, I present examples to frame Resource-Based Learning Environments (RBLEs) from different contexts. A description of the underlying infrastructure of RBLEs follows. Secondly, I discuss of how RBLEs can open opportunities within a learning environment, regardless of the context followed by some obstacles that can hinder RBLE implementation. Finally, suggestions for implementation and future research are provided.